Systems Reliability for 3D Steel Frames Subject to Gravity Loads. (November 2016) - Liu, Wenyu; Rasmussen, Kim J.R.; Zhang, Hao
Abstract: The system-based design of steel structures using advanced analysis leads to a more efficient structural design process and achieves a more uniform level of structural system reliability. The main impediment to adopting this method in practical applications is the apparent difficulty in assigning an appropriate resistance factor to structural systems. In this paper, the reliability assessment and derivation of system resistance factors for a series of 3D low-to-mid-rise steel frames are presented, taking into account the inherent uncertainties in material and geometric properties, and the model uncertainty of advanced analysis. Braced and unbraced (sway) frames with regular and irregular configurations are analysed under gravity loads and the system resistance factors are derived for different target reliability levels. The frames are selected to provide different system failure modes such as sway instability and/or member failure. Recommendations are made for the appropriate target reliabilities and associated system resistance factors for use in designing 3D steel frames at system level by advanced analysis.